Acidic Deposition and Climate Warming as Drivers of Tree Growth in High-Elevation Spruce-Fir Forests of the Northeastern US - Wason, Jay W.; Beier, Colin M.; Battles, John J.; Dovciak, Martin (Frontiers in Forests and Global Change, 2019)
Acid rain in eastern North America contributed to the widespread decline of red spruce in high-elevation spruce-fir forests. With recent reductions in acid deposition and a warming climate, resurgence of red spruce growth has been reported in some mountain areas. Based on an extensive tree-ring sampling network established across elevations (600 to 1200 m above sea level) in spruce-fir forests on 10 mountains in the northeastern US (New York, Vermont, New Hampshire, and Maine), we investigated whether this resurgence was specific only to red spruce or if it occurred also in the codominant balsam fir. Furthermore, we tested if tree growth changes for both species were related to recent trends in acidic deposition and climate. Sharply increasing growth rates of red spruce were evident at all elevations and most closely correlated with increasing rainwater pH. Although climate of the previous year (cool July and warm November) explained higher spruce growth in certain years, recent trends in climate did not drive observed increases in spruce growth. In contrast, balsam fir exhibited no regional growth surge during the period of spruce recovery. Thus, spruce growth resurgence appears to be mediated primarily by declining acid deposition and not climatic changes or stand dynamics that would also impact fir growth. Although high-elevation forests may ultimately be at risk for future warming-related heat and drought stress, the observed recent dramatic resurgence of spruce growth illustrates the benefits of policy-driven reductions in acidic deposition for the health and productivity of northeastern US forests.